2021
DOI: 10.48550/arxiv.2110.12651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Doping evolution of superconductivity, charge order and band topology in hole-doped topological kagome superconductors Cs(V$_{1-x}$Ti$_x$)$_3$Sb$_5$

Abstract: The newly discovered Kagome superconductors AV3Sb5 (A = K, Rb, Cs) exhibit superconductivity, charge order, and band topology simultaneously. To explore the intricate interplay between the superconducting and charge orders, we investigate the doping evolution of superconductivity, charge-density-wave (CDW) order and band topology in doped topological kagome superconductors Cs(V1−xTix)3Sb5 where the Ti-dopant introduces hole-like charge carriers. Despite the absence of the CDW phase transition in doped compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 43 publications
0
14
1
Order By: Relevance
“…Previous high-pressure measurements on this kagome metal system AV 3 Sb 5 show that superconductivity coexists with CDW order under ambient pressure, however superconducting T c increases while T CDW decreases with increasing pressure, suggesting a competition between CDW order and superconductivity [9,25,34,35]. Evidence for such competition is also provided by holedoping studies [34,36,37], systematic studies of finite crystal thickness [34,38], and measurements under uniaxial strain [39]. In contrast, our x-ray results on the ambient pressure CDW state in CsV 3 Sb 5 show it to be robust and to co-exist well with its superconducting instability below T c = 2.9 K, at least as low as T = 2 K.…”
mentioning
confidence: 57%
“…Previous high-pressure measurements on this kagome metal system AV 3 Sb 5 show that superconductivity coexists with CDW order under ambient pressure, however superconducting T c increases while T CDW decreases with increasing pressure, suggesting a competition between CDW order and superconductivity [9,25,34,35]. Evidence for such competition is also provided by holedoping studies [34,36,37], systematic studies of finite crystal thickness [34,38], and measurements under uniaxial strain [39]. In contrast, our x-ray results on the ambient pressure CDW state in CsV 3 Sb 5 show it to be robust and to co-exist well with its superconducting instability below T c = 2.9 K, at least as low as T = 2 K.…”
mentioning
confidence: 57%
“…These results establish a solid foundation to study the interplay between the primary and secondary CDW order parameters in kagome metal system. They guide to identify the primary and secondary order parameters as well as their interplay, when these CDW order parameters are tuned by carrier doping [26][27][28], external pressure [24,25], or strain [66]. We choose êi and ês to be X, Y , R, and L, where X = (1 0 0), Y = (0 1 0), R = 1/ √ 2 (1 i 0), and L = 1/ √ 2 (1 − i 0).…”
Section: Discussionmentioning
confidence: 99%
“…in AV 3 Sb 5 , as T c increases when the CDW order is suppressed by hydrostatic pressure [24,25], or by the hole doping [26][27][28], or by thickness reduction [28,29]. Furthermore, the CDW state shows a large extrinsic anomalous Hall effect [30,31] in the absence of magnetic ordering [32].…”
mentioning
confidence: 99%
“…First principles calculations could relate our phase diagram to these experiments by determining δ, µ and couplings as a function of pressure. Variation of doping and pressure indicates the presence of two distinct superconducting phases [46][47][48]; it is possible that the TvHS dominates the physics in one doping regime, while other interaction physics could be important elsewhere in the phase diagram [82][83][84][85][86][87]-e.g. it has been shown that sublattice interference near the K-points can result in higher-order topological multigap s-or p-wave states [11,86,87].…”
Section: Discussionmentioning
confidence: 99%